Poetic thefts in Al-Farazdaq's poetry - Al-Hamoud, Maher Ennad (Journal of Humanities & Social Sciences, 2021)
The research studies the issue of poetic thefts at Al-Farazdaq, relying on the classifications of the ancient critics, trying to reveal what were the reasons that prompted the poet to steal, studying the critical issue and their types of theft in the poet's poetry, , and critics' opinions on the issue of taking poet from other poets. It has an ancient history of our Arab literature dating back to the first early Arab poetry. Research has studied the types of robberies found in in the poet's poetry.Raiding, usurpation plagiarism the Impersonation, the Vilification and its reasons for the desire of the poet to acquire the unique verses that fit his doctrine of pride. So the search consisted of two researchers and one finalist, the first researcher took up thefts and their types in the hair of the frieze. And the poet's knowledge of it, and the research showed the critics' view of Al Farazdaq thefts. The second researcher studied thefts statistically explaining the way in which poets were taken and how many poets were The second researcher studied thefts statistically explaining how many poets had acquired their poets and how many poets had acquired their poetry. Poetic theft is an important phenomenon that requires research, study and further elaboration of its monetary and psychological impact.
Keywords: Al Farazdaq; abandoned words; taking robberies; raiding; impersonation; fabrication